Factors of importance to 30-day survival after in-hospital cardiac arrest in Sweden – A population-based register study of more than 18, 000 cases. (15th March 2018) - Hessulf, Fredrik; Karlsson, Thomas; Lundgren, Peter; Aune, Solveig; Strömsöe, Annelie; Södersved Källestedt, Marie-Louise; Djärv, Therese; Herlitz, Johan; Engdahl, Johan
Abstract: Background and objective: In-hospital cardiac arrest (IHCA) constitutes a major contributor to cardiovascular mortality. The aim of the present study was to investigate factors of importance to 30-day survival after IHCA in Sweden. Methods: A retrospective register study based on the Swedish Register of Cardiopulmonary Resuscitation (SRCPR) 2006–2015. Sixty-six of 73 hospitals in Sweden participated. The inclusion criterion was a confirmed cardiac arrest in which resuscitation was attempted among patients aged > 18 years. Results: In all, 18, 069 patients were included, 39% of whom were women. The median age was 75 years. Thirty-day survival was 28.3%, 93% with a CPC score of 1–2. One-year survival was 25.0%. Overall IHCA incidence in Sweden was 1.7 per 1000 hospital admissions. Several factors were found to be associated with 30-day survival in a multivariable analysis. They included cardiac arrest (CA) at working days during the daytime (08–20) compared with weekends and night-time (20–08) (OR 1.51 95% CI 1.39–1.64), monitored CA (OR 2.18 95% CI 1.99–2.38), witnessed CA (OR 2.87 95% CI 2.48–3.32) and if the first recorded rhythm was ventricular fibrillation/tachycardia, especially in combination with myocardial ischemia/infarction as the assumed aetiology of the CA (OR for interaction 4.40 95% CI 3.54–5.46). Conclusion: 30-day survival after IHCA is associated with the time of the event, the aetiology of the CA and the degree of monitoring and this should influence decisions regarding the appropriate level of monitoring and care. Highlights: 30-day (28.3%) and one year (25.0%) survival was high among > 18000 IHCA cases reported to the Swedish Register for CPR 2006-2015. Overall IHCA incidence in Sweden was 1.7 per 1000 hospital admissions in the year 2015. Multiple factors were associated with 30-day survival including the time of the event, the aetiology of the CA and the degree of monitoring. An increased level of monitoring and care of the right individual based on factors associated with survival should improve survival following IHCA.